Non-invasive measurement of endothelial function: effect on brachial artery dilatation of graded endothelial dependent and independent stimuli. Issue 1 (July 1997) - Leeson, P.; Thorne, S.; Donald, A.; Mullen, M.; Clarkson, P.; Deanfield, J.
Abstract : OBJECTIVE: To examine the relation between endothelial dependent and endothelial independent stimuli of varying intensity and measures of vascular function in the brachial artery of young healthy adults, to determine whether these responses are consistent and can be used to assess endothelial function. DESIGN AND SETTING: High resolution ultrasound was used to measure brachial artery diameter at rest, after reactive hyperaemia induced by forearm cuff occlusion, and after sublingual isosorbide dinitrate (ISDN). Each subject was assigned to a random order of six cuff occlusion times (30 seconds, 1.5, 2.5, 3.5, 4.5, and 8 minutes) and six doses of ISDN (10, 20, 50, 100, 200, and 400 micrograms). SUBJECTS: Three males and three females mean age 31 years (range 25 to 43) with no known risk factors for cardiovascular disease. MAIN OUTCOME MEASURES: Flow mediated, endothelial dependent dilatation was compared to duration of cuff occlusion, peak reactive hyperaemia, and duration of increased flow. Nitrate induced, endothelial independent dilatation was compared to dose of ISDN and change in flow. RESULTS: Vessel dilatation and duration of peak flow change increased with longer duration of cuff occlusion. After 4.5 minutes of occlusion, flow mediated dilatation was mean (SD) 96 (6)% of maximal response and did not increase significantly with longer occlusion times. No significant dilatation occurred after 10 or 20 micrograms of ISDN in any subject. With increasing doses up to 200 micrograms there was an increase in dilatation. Endothelial independent dilatation did not increase significantly with doses of ISDN above 200 micrograms. CONCLUSIONS: Measures of arterial function vary with duration of blood flow occlusion and ISDN dose. Maximum arterial response was reached in all subjects after 4.5 minutes of blood flow occlusion or 200 micrograms of ISDN. Therefore, these variables produce consistent reproducible measures of endothelial function.